Digital tourism marketing: Case study of the campaign Can’t Skip Portugal - Parreira, C. (2022)
The theme of this study is the analysis of the advertising campaign "Can’t Skip Portugal" launched in 2017 by Tourism of Portugal, which the main objective was to show all the regions of the country, covering not only the most known areas but also to promote other areas of the country, showcasing Portugal as a potential destination for tourists. The objective of the study is to understand how this kind of Digital Marketing can be sufficiently appealing and arouse in-terest in the viewers. To reach the proposed objective, a qualitative research of descriptive type was carried out. Throughout this study it was possible to have a better understanding of the benefits of Digital Marketing. It could be con-cluded that the advertising campaign “Can’t Skip Portugal” achieved its pro-posed goals, involving and influencing the target audience in the choice of Portugal as a touristic destination.